Systematic assessment of atypical deletions reveals genotype–phenotype correlation in 22q11.2. Issue 11 (14th April 2005) - Rauch, A; Zink, S; Zweier, C; Thiel, C T; Koch, A; Rauch, R; Lascorz, J; Hüffmeier, U; Weyand, M; Singer, H; Hofbeck, M
Abstract : Introduction: Clinical variability associated with the common 22q11.2 microdeletion is well known, and has led to a broad application of FISH diagnostics with probes for loci TUPLE1 or D22S75 (N25), although, rarely reported atypical deletions associated with the same phenotypic spectrum would not be discovered by these probes. As most types of 22q11.2 deletions occur between low copy repeats within the region (LCR22), we assumed that atypical deletions should be more common than has been reported. To address this question and the possibility of a deletion size related genotype-phenotype correlation, we systematically assessed the frequency of typical and atypical 22q11.2 deletions in a large cohort of patients. Methods: We used a set of 10 fluorescent in situ hybridisation (FISH) DNA probes, capable of detecting all reported and hypothetical deletions between the LCR22, and analysed 350 patients. Deletion sizes in atypical deletions were established by use of further FISH probes. Frequency of certain atypical deletions was analysed in controls by FISH and quantitative PCR. Results: Patients with conotruncal heart defects (ctCHD) and with typical VCFS phenotype showed the common 3 Mb or nested 1.5 Mb deletions (in 18.5% and 78.6%, respectively), but no atypical deletion, while 5% (3/63) of patients with a mildly suggestive, atypical phenotype showed atypical distal deletions, which were not detected in patients with mental retardation of unknown origin or in healthy controls. Discussion: These statistically significant differences demonstrate that atypical distal 22q11.2 deletions are very uncommon in patients with ctCHDs, while atypical congenital heart defects and mild dysmorphism are recognisable feature of atypical distal deletions. Further phenotype-genotype analysis disclosed association of significant developmental delay with the distal part of the common deletion region, and choanal atresia and atypical CHDs with the adjacent distal deletion region.